Phase behavioural study of palm-based lauryl alcohol ethoxylates - Lim, Hong Ngee; Kassim, Anuar; Huang, Nay Ming; Abdullah, Dzulkefly Kuang; Abdullah, Abdul Halim; Yarmo, Mohd Ambar; Yeong, Shoot Kian (Universiti Putra Malaysia Press, 2008)
Palm-based lauryl alcohol ethoxylates were synthesized with different chain lengths of ethylene oxide using an ethoxylation reactor. The effect of changing the ethylene oxide chain length was investigated by reacting 3, 6 and 100 moles of ethylene oxide with palm- based lauryl alcohol. The samples were labeled as C12E3, C12E6 and C12E100. The 6 moles of ethylene oxide was approximately the same length as the palm-based lauryl alcohol. The chromatograms of C12Ex showed less retention peaks than the standard, Brij 40 (Tetraethylene glycol dodecyl ether - C12E4). Fourier Transformed Infrared Spectroscopy (FTIR) displayed a strong C-O stretch at 1120 cm-1 which was attributed to C-O single-bond stretching of the ether group. The ternary phase diagrams for a series of olive or olein oil/water/C12Ex systems were investigated at 25°C. The important features of the ternary phase systems are the emulsion and the concentrated emulsion phases. Optical microscopy revealed the difference in morphology between emulsion and concentrated emulsion. The particle size of the emulsions and the concentrated emulsions were in the range of 2.635 µm to 9.175 µm and 0.694 µm to 4.764 µm, respectively. The rheological flow curves measurement of the concentrated emulsion showed crossover of the ascendant and descendant curves which indicated structural build up of the sample instead of destruction.